Avaliação prospectiva de diferentes marcadores inflamatórios como preditores de evolução clínica e óbito em pacientes neutropênicos febris - Leticia Carvalho Neuenschwander (2009)
Fever in neutropenic patients represents a clinical challenge. While this condition carries a high risk of morbidity and mortality, the heterogeneity of patients evolution justifies a customized approach. Routinely used scores for risk stratification are based solely on clinical parameters. This study aimed to test the association of plasmatic levels of different inflammatory markers with some clinical endpoints in patients with FN, as following: 1) 28-day mortality; 2) early adjustment on antibiotic therapy; 3) persisting fever within three days of antibiotic therapy and; 4) bacteremia. The study was conducted at the University Hospital of the Federal University of Minas Gerais (HC-UFMG). All adult patients with febrile neutropenia admitted to the Hematology Service from September 2008 to March 2009 were evaluated for eligibility. Thirty seven episodes of febrile neutropenia occurring in 27 patients were included in the final analysis. Blood samples were taken at inclusion (D0), as well as at the first day (D1), third day (D3) and seventh day (D7) after the onset of fever. Nine different inflammatory markers were measured: interleukin 8 (IL-8), protein induced 10 (IP-10), tumor necrosis factor alpha (TNFa) and its two soluble receptors, type I and type II (sTNFRI and sTNFRII), monocytechemotactic protein (MCP-1), macrophage inflammatory protein 1 (MIP-1a), procalcitonin (PCT) and eotaxin (Eotax) Median age was 36 years (range; 19 to 64 years). Most frequent diagnoses were acute myeloid leukemia (37%), and non- Hodgkin's lymphoma (24%). PCT measured on D0 (cutoff value 2.27 . g / L; sens 66.7%, esp 100%; p = 0.03), sTNFRII measured on D1 (cut value: 3,740 pg / ml; sens 88%, esp. 54%; p = 0.05), Delta D3-D1 of IL-8 (cutoff +320 pg / ml; sens 44%, esp 96%; p = 0.048) and delta D3-1 of eotax (cutoff: 43 pg / ml; sens 44%,esp 94%; p = 0.026) were significantly higher in patients who died within 28 days of follow-up as compared to their surviving counterparts. Early adjustment on antimicrobial treatment (within the first three days) was associated with higher levels of IL-8 (cutoff value 217.9 pg / ml, 72% sens, esp 80%; P = 0.047), sTNFRII (cutoff 3,992 pg / ml; sens 72%, esp 88% esp; p = 0.036) and MCP-1 (cutoff 1,522 pg / ml; sens 72%, esp 84%; p = 0.008) measured three days after fever onset. No inflammatory marker was associated with bacterial blood stream infection.Conclusion: PCT, IL-8, sTNFRII, MCP-1 and eotax seems to be useful markers to assess the risk of death in febrile neutropenic patients and the need ofearly adjustment on antimicrobial treatment. IP10, MIP1-a, sTNFRI, TNFa showed no association with any endpoint evaluated.